Comparative Analysis of Linear Controllers used for Grid Connected PV System - Ritesh Dash; Sarat Chandra Swain; Sanhita Mishra (Institute of Advanced Engineering and Science, 2018)
Requirement for electrical energy is increasing in a ramp function manner. To meet the steady increasing in energy demand it is required to find some alternate source of energy. Except the conventional source of energy one type of renewable energy i.e PV may be regarded as a clean source of energy to meet the energy demand. PV modules generating DC power cannot be directly connected to the electrical infrastructure as most of the grid infrastructure uses either 230volt or 120 volt. Therefore power electronic device most be connected (inverter) between PV and grid. In order to make a competitive market between the renewable generated power and conventional way of generating the power it is required to design a cost effective inverter, qualitative output which is pure sinusoidal and harmonics free. In this paper a comparative analysis among the various linear controllers are presented. Proposed Optimised PID Controller is Presented through MATLAB Simulink based environment.